Nasal angioleiomyoma in 2 dogs - Schuenemann, Riccarda; Geyer, Claudia; Pohl, Sabine; Ludewig, Eberhard; Oechtering, Gerhard (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2024)
This case report describes 2 dogs, an Appenzeller Mountain dog and an Irish Wolfhound, with angioleiomyoma within the nasal cavity. Endoscopic surgical resection resulted in cure in both dogs. Macroscopically and on diagnostic imaging, tumor masses may appear malignant because of local turbinate destruction. This highlights the importance of histological examination before any recommendations are made to owners because tumors of the nasal cavity may be benign and surgery curative.
Keywords: Nasal angioleiomyoma; endoscopic surgery; benign tumor treatment; intranasal surgery